Kepemimpinan Madrasah Efektif dalam Peningkatan Mutu Madrasah Ibtidaiyah Al-Faat 2 Banggo Dompu - Muhasir Muhasir (Sekolah Tinggi Agama Islam (STAI) Al-Amin Dompu, 2020)
The purpose of this study was to find out why effective madrasah leadership is needed in improving the quality of madrasah at MI Al-Faat 2 Banggo Dompu and how to implement effective madrasah leadership at MI Al-Faat 2 Banggo Dompu. This type of research used in this research is a qualitative approach with a phenomenological approach. The data collection technique is done by interview, observation, and documentation. The subjects in this study were the head of the madrasah, the chairman of the committee, the head of the foundation, the teachers, and the students. The results showed that: (1) Madrasah leadership is effective in improving the quality of madrasahs carried out by the head of madrasah Miftahul Akhlaqiyah is to always establish a clear focus on the objectives of developing madrasah quality and student achievement both in madrasah and outside madrasah, (2) effective madrasah leadership who always play a collective leadership role and play an example at all levels of activity in madrasah and outside madrasah so that they appear as role models, (3) Evaluating the development of teacher and student performance, so that teacher and student achievement can achieve maximum goals. So that the impact of this effective madrasah leadership is to increase the morale of madrasah teachers, increase the effectiveness of madrasah staff and teacher teamwork, and can improve student learning achievement optimally.